The Necrotroph Botrytis cinerea BcSpd1 Plays a Key Role in Modulating Both Fungal Pathogenic Factors and Plant Disease Development - Chen, Huchen; He, Shengnan; Zhang, Shuhan; A, Runa; Li, Wenling; Liu, Shouan (Frontiers in Plant Science, 2022)
Botrytis cinerea is a necrotrophic microbe that causes gray mold disease in a broad range of hosts. We conducted molecular microbiology and transcriptomic analysis of the host - B. cinerea interaction to investigate the plant defense response and the fungal pathogenicity. Upon B. cinerea infection, plant defense responses were changed from the activation to repression, thus the expression of many defense genes decreased in Arabidopsis thaliana. B. cinerea Zn(II)2Cys6 transcription factor BcSpd1 involved in the suppression of plant defense as ∆BcSpd1 altered wild-type B05.10 virulence by recovering part of the defense responses at the early infection stage. BcSpd1 affected genes involved in the fugal sclerotium development, the infection cushion forming, the biosynthesis of melanin and the change of environmental pH values, which were reported to influence fungal virulence. Specially, BcSpd1 bound to the promoter of the gene encoding quercetin dioxygenase (BcQdo) and positively affected the gene expression, which was involved in catalyzing anti-fungal flavonoids degradation. This work indicated BcSpd1 played a key role in the necrotrophic microbe B. cinerea virulence towards plant by regulating pathogenicity related compounds thereby suppressed early plant defense.